Generalized rational α_*- contraction in C^*- algebra-valued b-metric spaces - Mohamed Rossafi; Hafida Massit; Abdelkarim Kari (Department of Mathematics, Hasanuddin University, 2022)
This present paper extends some common fixed point theorems for generalized rational α_*- contraction of multi-valued mappings in the setting of C^*- algebra-valued b-metric spaces .